Hip-Spine Syndrome: Acetabular Anteversion Angle Is Associated with Anterior Pelvic Tilt and Lumbar Hyperlordosis in Patients with Acetabular Dysplasia. Issue 1 (28th March 2019) - Okuzu, Yaichiro; Goto, Koji; Okutani, Yuki; Kuroda, Yutaka; Kawai, Toshiyuki; Matsuda, Shuichi
Abstract : Background: Hip-spine syndrome was originally described by Offierski and MacNab, who argued that the flexion deformity of the hip rotated the pelvis forward, causing the spine symptoms. We additionally hypothesized that in patients who have osteoarthritis (OA) of the hip, the pelvis is tilted anteriorly to compensate for the anterior acetabular coverage defect. We investigated the hip factors associated with anterior pelvic tilt (PT) in patients who had OA of the hip due to acetabular dysplasia. Methods: We retrospectively reviewed the medical records of patients who had undergone total hip arthroplasty between January 2009 and December 2017 to identify those who had unilateral secondary OA due to acetabular dysplasia. Patients who had spinal imbalance, a history of spinal or lower limb fracture or surgery, bilateral OA of the hip, or a severely subluxated hip were excluded, leaving 100 eligible patients. We defined the indicators of an anterior acetabular coverage defect, flexion deformity of the hip, and anterior PT as the acetabular anteversion angle (AAA), extension range of motion (ROM), and anterior tilt of the pelvis, respectively. We measured hip factors and spinal parameters on radiographs and the standardized axial and coronal planes on 3-dimensional computed tomography with reference to the anterior pelvic plane. Hip factors associated with PT were investigated. Results: Univariate analysis showed a significant correlation between PT and both AAA (r = –0.389, p < 0.001) and combined anteversion angle (r = –0.272, p = 0.03). Multivariate regression analysis identified AAA (β = –0.385, p < 0.001) and extension ROM (β = 0.212, p = 0.0496) as independent factors associated with PT. Lumbar lordosis and pelvic incidence minus lumbar lordosis were significantly correlated with AAA, but sagittal vertical axis was not. Conclusions: When treating patients who have acetabular dysplasia, surgeons should recognize the relationship between the anterior acetabular coverage and anterior PT. Correcting hyperlordosis of the lumbar spine can induce progression of hip OA because it may decrease the acetabular anterior coverage.